2019
DOI: 10.1177/0018726719846264
|View full text |Cite
|
Sign up to set email alerts
|

Beyond time-binds: Rethinking work–family dynamics for a mobile world

Abstract: Contemporary work is increasingly mobile, sparking new challenges for scholars of work and organizations. In this review article, we argue that a ‘mobilities lens’ offers strong potential for rethinking established approaches, focusing on one important sub-field: work–family studies. Drawing on a ‘problematization’ approach (Sandberg and Alvesson, 2011) and a systematic literature review (SLR) of work–family research published from 1995 to 2015, we show how theoretical assumptions about time, space, and place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 135 publications
(187 reference statements)
0
11
0
2
Order By: Relevance
“…This phenomenon may explain the inconsistent findings reported by prior research, regarding the effects of working remotely. Indeed, whereas some studies have demonstrated desirable effects of working remotely on various facets of employees' recovery and on personal and professional well-being (Biron and van Veldhoven, 2016;Charalampous et al, 2019), others have shown that working remotely could also be linked to higher levels of guilt and overcommitment due to employees' desire to reciprocate for the increased flexibility offered by their organization (Hughes and Silver, 2020). These diverging results may suggest that working remotely versus on-site could moderate the effects of SE on emotional exhaustion, rather than play a direct role.…”
Section: The Undesirable Effects Of Emotional Exhaustionmentioning
confidence: 99%
“…This phenomenon may explain the inconsistent findings reported by prior research, regarding the effects of working remotely. Indeed, whereas some studies have demonstrated desirable effects of working remotely on various facets of employees' recovery and on personal and professional well-being (Biron and van Veldhoven, 2016;Charalampous et al, 2019), others have shown that working remotely could also be linked to higher levels of guilt and overcommitment due to employees' desire to reciprocate for the increased flexibility offered by their organization (Hughes and Silver, 2020). These diverging results may suggest that working remotely versus on-site could moderate the effects of SE on emotional exhaustion, rather than play a direct role.…”
Section: The Undesirable Effects Of Emotional Exhaustionmentioning
confidence: 99%
“…The small but growing literature on human relations in FIFO regimes tends to favor spatial over temporal relations, with a growing emphasis on worker experiences of multi-local being and mobility ( Barber, 2018 ; Gorman-Murray and Bissell, 2018 ; Jones and Southcott, 2015 ; Saxinger, 2016 ) and gendered experiences of work and family across the sites of work and home ( Barber, 2016 ; Dorow and Mandizadza, 2018 ; Jean, 2019 ; Mayes, 2020 ; Saxinger, 2016 ). As Hughes and Silver (2020) point out, this attention to spatial mobility provides an important corrective to work–family studies’ emphasis on time. However, organizational studies, FIFO research (and mobility studies more generally—see Sheller, 2019 ), and scholarship on the ‘time of oil’ have largely neglected the work camp as a specific kind of organization with distinctive temporalities (see Straughan et al, 2020 for one recent exception).…”
Section: Theorizing Camp Timementioning
confidence: 99%
“…En el escenario del teletrabajo, los procesos autorregulatorios se encuentran mediados de modo importante por instrumentos auxiliares externos, promoviendo el desarrollo tanto, de esquemas que permitan identificar contextos y modalidades pertinentes de actividad, como de modulación del comportamiento (Vygotsky, 1981). Las TIC, al igual que los distintos soportes y dispositivos (agendas, ayuda memoria, calendarios…) no solo permitirían "trabajar en cualquier momento y en cualquier lugar" (Hughes & Silver, 2020), sino que también incidirían en la forma y contenidos de la propia actividad, operando ya sea como herramientas principales, complementarias o sustitutas de las funciones a ejecutar (Díaz, 2008). En ese contexto, los instrumentos técnicos, en análogo título que los instrumentos psicológicos, asumirían una función de mediación entre el individuo y la realidad, así como del individuo consigo mismo (Vygotsky, 1997).…”
Section: Regulaciones Organizacionales Instrumentales Y Contextualesunclassified
“…La pandemia por COVID-19 ha implicado una importante expansión del trabajo remoto, trasladando en forma masiva la actividad laboral desde la presencialidad al teletrabajo (Chong et al, 2020). Así, el actual escenario ha significado: a) una extensión de esta práctica a nuevos grupos; b) una expansión creciente del teletrabajo hacia el tiempo libre, fuera del horario normal de trabajo, compitiendo con la vida privada, dada su rápida e improvisada implementación; y c) una expansión de las tecnologías de la información y la comunicación (TIC) en uso, diluyendo las fronteras tempo-espaciales (Thulin et al, 2019;Hughes & Silver, 2020).…”
Section: Introductionunclassified